Board audit committee and corporate insolvency. Issue 3 (11th September 2017) - Appiah, Kingsley Opoku; Amon, Chizema
Abstract : Purpose: The purpose of this paper is to examine whether the presence, expertise, independence, size and meetings of the audit committee (AC) have an effect on corporate insolvency. Design/methodology/approach: The authors use 1, 835 firm-year observations for 98 insolvent and 269 solvent UK-listed non-financial firms from 1994 to 2011. Findings: The authors find that corporate insolvency is negatively related to the meetings and independence of the AC but not to AC's presence and size. The authors also observe that financial expertise on the AC is not related to corporate insolvency. These associations are robust to different specifications, while after controlling for board composition, board size, the number of board meetings, CEO duality, financial and firm characteristics. Research limitations/implications: The study's approach has two main limitations: neglect of small and medium private unquoted firms and more regulated corporate governance environment. Practical implications: The findings lend support to the continual use of the agency theory as an explanation in understanding the role of the analytical lens through which to study the efficacy of the AC in reducing the likelihood of insolvency. Social implications: The findings support continued efforts to strengthen boards' ACs in the wake of high profile insolvencies. The findings will assist regulators and firm management to design appropriate ACs (e.g. independence) and processes (e.g. number of meetings). Originality/value: The authors provide empirical evidence on the impact of the AC on firm insolvency in the UK context, an important but neglected area in research.